Black ice : a thriller - Thor, Brad (Thor, Brad. Scot Harvath., 2021)
"Scot Harvath is having his best summer ever. With a cottage on the fjord, a boat, and his beautiful girlfriend Sølvi, he's got everything he could possibly want. But out of vacation days and long overdue back home, America's top spy has a decision to make-return, or submit his resignation"--